Glemt, genfundet og genfortolket: Det romanske vesttårn i Rindum Kirke, Vestjylland - Larsen, Morten; Mikkelsen, Hans (Kuml, 2025)
Forgotten, rediscovered and reinterpreted The Romanesque west tower of Rindum church In connection with restoration works carried out in 2022 on Rindum church, West Jutland, the National Museum of Denmark had the opportunity to undertake a series of archaeological surveys. These concluded that the church had a west tower already during the Romanesque period (figs. 1-7). This Romanesque tower was an integrated part of the western end of the nave with a smaller free-standing upper section rising above the nave (fig. 8). Romanesque towers are a far from common feature of Danish churches, with the majority being found in eastern Denmark. The Rindum tower is therefore a valuable addition to the rare examples of Romanesque west towers in Jutland, with only few parallels in western Denmark (figs. 9-10). In conjunction with the archaeological survey, the functions and interpretations of Romanesque towers were scrutinized. The common interpretation of these towers as symbols of aristocratic power and the seat of church patrons is challenged with reference to recent European research emphasizing their liturgical significance. Altars and, to some extent, burials and murals in the tower vestibules and upper storeys, link the towers to predominantly liturgical functions emphasizing the rites of death and memory, the cult of St. Michael and/or baptism. The significant geographical distribution of the towers in medieval Denmark is interpreted as mirroring the diversity in early medieval settlement patterns and the related liturgical needs of the population, rather than differences in an aristocratic landscape.